Ok, this one I think I can get. The answer is 2. s = sqrt(2 + sqrt(2 + sqrt(2+...)))s^2 = 2 + sqrt(2 + sqrt(2 + sqrt(2+...)))s^2 = 2 + ss^2 - s - 2 = 0s = 2, -1The negative root makes no sense in this case, leaving s = 2.
Hey, how come your trolls never seem to post on these threads? Mathematical reasoning is a little intimidating, I suppose.
There is a slightly simpler way to look at it as well and that is to notice that, if you let "s" be the solution, then:s = sqrt(2 + s)The answer falls out of that pretty quickly.
Post a Comment
3 comments:
Ok, this one I think I can get. The answer is 2.
s = sqrt(2 + sqrt(2 + sqrt(2+...)))
s^2 = 2 + sqrt(2 + sqrt(2 + sqrt(2+...)))
s^2 = 2 + s
s^2 - s - 2 = 0
s = 2, -1
The negative root makes no sense in this case, leaving s = 2.
Hey, how come your trolls never seem to post on these threads? Mathematical reasoning is a little intimidating, I suppose.
There is a slightly simpler way to look at it as well and that is to notice that, if you let "s" be the solution, then:
s = sqrt(2 + s)
The answer falls out of that pretty quickly.
Post a Comment